Gestión presupuestaria del Gobierno Autónomo Descentralizado Rural de la parroquia la Unión en el periodo 2022 - Guerrero Oñate, Nicole Lourdes (2024)
This case study deals with the detailed analysis of the budget execution of the Rural Decentralized Autonomous Government of the La Unión parish, focusing on the period 2022. The research arises from the need to understand how budget decisions influence the effectiveness and efficiency of local public management, and how these impact the socioeconomic development of the community. Through a meticulous review of budget statements, this study seeks not only to identify the current state of income and expenses, but also to evaluate compliance with financial objectives and the responsiveness of the parish government to the needs of its inhabitants. Using a quantitative methodology, this work is supported by a documentary review of budget records, complemented by the application of management indicators as key tools to interpret effectiveness, efficiency, and budget compliance. This approach allowed not only a deep understanding of the financial management of the La Unión Parish GAD, but also the identification of areas for improvement and the proposal of recommendations focused on optimizing resources and processes.